The Influence of Fiqh Thaharah Learning on Changes in Student Behavior in Maintaining Purity at MI Al Ula Balikpapan - Anisa Anisa; Alfi Taufik (Madrasah Al-Wathoniyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to determine the influence of Fiqh Thaharah learning on students’ behavioral changes in maintaining purity at MI Al Ula Balikpapan Barat. This research employs a quantitative descriptive approach using simple linear regression analysis. The population consists of all 58 fifth-grade students of MI Al Ula Balikpapan Barat, all of whom were included as samples through a saturated sampling technique. Data were collected through questionnaires based on indicators of Fiqh Thaharah learning and cleanliness behavior. The t-test results show that the calculated t-value of 4.678 is higher than the table value of 2.63157 at a 5% significance level, indicating a significant influence between Fiqh Thaharah learning and students’ behavioral changes in maintaining purity. The significance value of 0.001 (<0.05) further confirms that Fiqh Thaharah education plays an essential role in enhancing students’ awareness of cleanliness and spiritual purity. Therefore, Fiqh Thaharah learning not only improves students’ conceptual understanding of Islamic teachings but also cultivates discipline, responsibility, and spiritual awareness in their daily lives.